Online Tools in Providing Feedback in Management - Iryna Piatnychuk; Iryna Boryshkevych; Antonina Tomashevska; Iryna Hryhoruk; Dariusz Sala (Vasyl Stefanyk Precarpathian National University, 2022)
The article deals with the issue of online tools in providing feedback in management in today's dynamic environment. The article aims to study the use of modern online services for the organization of feedback in management and identify opportunities for their wider use. It is investigated that the application of the concept of feedback has a broad functional field: in the public sphere for the establishment of public feedback from the public; in the field of business - to determine the needs and levels of customer and consumer satisfaction; in general, in the production and services sectors to conduct research and improve the level of implementation of their main processes. It is established that by providing feedback, employees can receive information that will help them improve their tasks, reduce uncertainty and explore prospects for new tasks, as well as develop a sense of responsibility in employees. One of the most common forms of feedback is a survey, which collects information about the object of study during direct or indirect communication between the interviewer and the respondent. With online survey tools, you can quickly organize and analyze their results, provide feedback and offer information that can be useful in management reporting or to implement various opportunities. Based on the study, it is proposed to classify services according to the following characteristics: time-based online tools for instant and delayed (non-real-time) feedback; taking into account the involvement of respondents, online tools for cooperation, for evaluation. You can use online tools such as Mentimeter, and Kahoot to get real-time feedback. To conduct online surveys in real-time, you can use online tools: Survio, Surveymonkey, Google Forms, and Typeform. Classtime, Socrative, Quizalize, and Quizizz platforms can be used for evaluation. Services that help in establishing cooperation and receiving feedback are Padlet, Jamboard, Linoit, and Google Presentations. It is established that, depending on the purpose of the survey and the form of feedback, it is advisable to use appropriate online tools, taking into account the conditions of the organization of feedback. The study results are the basis for further research in terms of more effective use of modern online tools for feedback in management.